Gestural calligraphy as a trigger for the aesthetic experience of poetry. A fun and educational activity based on Cy Twombly's pictorial work for the understanding of poetic texts (Jóvenes en la Ciencia, 2025)
Development and analysis of classroom-based teaching exercises aimed at addressing difficulties identifiedin the reading of complex poetic texts among young groups of high school and college students. Theories andmethods from the visual arts, particularly the poetics and work of artist Cy Twombly, were used as a basis fordesigning the practical sessions.The responses and results of the pilot group's implementation of the practice were studied from the perspectiveof multidimensional systemic pedagogy to determine its feasibility and effectiveness in addressing poetic textsat three different levels: recognition of their structure, the plain and underlying meaning of the poems, andunderstanding of the aesthetic experience resulting from reading poems.